A novel association of ocular neuromyotonia with brainstem demyelination: Two case reports. (September 2014) - Menon, Deepak; Sreedharan, Sapna Erat; Gupta, Maneesh; Nair, MD
Ocular neuromyotonia (ONM) is a rare disorder of ocular mal-alignment in which painless, transient spontaneous or gaze-induced abnormal deviation of the eye manifests as episodic diplopia. With only a few cases reported in the literature, ONM mostly follows months to years after cranial irradiation for sellar or suprasellar lesions. Here we present two patients with this rare ocular condition, secondary to brainstem demyelination, the association of which is hitherto unreported in the literature. Both patients were 15-year-old girls who presented to us with episodic forced-eye deviation with diplopia. Examination during these attacks revealed ONM involving the superior rectus and medial rectus in the first and second patient, respectively. There was clinical evidence of intrinsic brainstem involvement with downbeat nystagmus and skew deviation in one patient without any other cerebellar or long tract signs. MRI showed evidence of demyelination involving the brainstem in both, with CSF showing positive immunological markers and with positive aquaporin-4 antibody in one patient. Both patients responded remarkably to immunomodulatory therapy and are asymptomatic at follow-up. That ONM can occur with brainstem demyelination has not been reported in the literature. This association may help in explaining the pathophysiology of ONM as secondary to segmental demyelination.